Victor Pelevin's Novel about Vampires as the form of Reflection on Postmodernism - Bobileva, Anastasya L.; Prokhorova, Tatyana G.; Bogdanova, Olga V. (Journal of History Culture and Art Research, 2017)
The current stage of culture development is usually defined as post-postmodern. Although this term is not well established and is interpreted differently, in any case it involves the overcoming of postmodernism. In Russian literature we should mention Victor Pelevin among the authors, whose works demonstrate the post-postmodernist tendencies most clearly. The evolution of his prose testifies that the postmodern worldview and the very mechanism of postmodern writing has become the subject of critical reflection in the late works of the writer. The novel by V. Pelevin "Empire V" (2006) is the material of the analysis in the article. The aim of the study is to reveal the nature and the forms of postmodernism reflection manifested in this work. During the analysis the authors established that Pelevin plays with a popular genre of mass culture - a novel about vampires, using it as a kind of metaphorical way to clarify the nature of postmodern literature, which appropriates, absorbs and exploits the forms, ideas and motives earlier developed in culture. Postmodernists, like vampires, borrow information from different sources and use "someone else's blood" for their own purposes. Combining the "languages" of mass and elite cultures, activating the intertextual links, Pelevin eventually pursues antipostomodernist goals: he reveals the totality of the simulativity, proves that mass culture is ready to absorb postmodernism, and turn it into an empty signifier. This can be defined as a kind of cultural reflection, as a form of the self-reflection and writer’s cognition on the state of modern culture.